Regional Versus General Anesthesia: Effect of Anesthetic Techniques on Clinical Outcome in Lumbar Spine Surgery. Issue 1 (January 2020) - Baenziger, Bertram; Nadi, Najia; Doerig, Ramon; Proemmel, Peter; Gahl, Brigitta; Hodel, Daniel; Hausmann, Oliver N.
Abstract : Background: There are only a few prospective clinical trials investigating the effects of different anesthetic techniques on clinical outcomes after lumbar spine surgery. The purpose of this study was to evaluate clinical outcomes in patients receiving general (GA) and regional anesthesia (RA) for lumbar spine surgery. Methods: This was a single-center, 2-arm, trial in which 100 patients undergoing lumbar spine surgery were randomized to receive either RA or GA (50 per group). The primary endpoint was morphine consumption during the first postoperative 48 hours. In addition, anesthesia time, transition time (defined as time from end of surgery to admission to the postoperative anesthesia care unit), visual analogue scale (VAS) for pain, and patient satisfaction at hospital discharge were recorded. Results: There was no difference in the primary endpoint (cumulative morphine consumption at 48 h) between the 2 anesthesia types. Anesthesia and transition times were significantly shorter in the RA compared with the GA group—anesthesia time 125.4±23.6 minutes for GA versus 99.4±13.5 minutes for RA, transition time 22.5 minutes for GA versus 10.0 minutes for RA (both P <0.001). The VAS for pain on arrival to the postoperative anesthetic care unit was lower for patients who received RA compared with GA (crude and adjusted, both <0.001). 84% of patients in the RA group were completely satisfied compared with 74% in the GA group ( P <0.001). There was a significant difference in the sex analysis for VAS for pain over time; females reported higher VAS for pain from the preoperative assessment to 6 weeks after the operation ( P <0.001). Conclusions: There was no difference in postoperative morphine consumption in patients receiving GA and RA for lumbar spine surgery. RA was associated with shorter anesthesia and transition times, lower VAS for pain at arrival at the postoperative anesthesia care unit, and higher patient satisfaction at hospital discharge.